2015
DOI: 10.1073/pnas.1508766112
|View full text |Cite
|
Sign up to set email alerts
|

Human impacts on fisheries across the land–sea interface

Abstract: A long-held paradigm is that estuaries are important to the welfare of estuarine-dependent coastal fisheries, providing spawning areas, suitable salinity gradients for development, protection from predators, and food. Many publications link the beneficial nature of estuaries with fisheries production and decry human activities that modify habitat, and therefore potentially decrease fisheries production. However, what if the water quality of the estuary, often human-driven, results in less than suitable habitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Relevant keywords used in search Toxicants and Pollutants "xenobiotics" or "toxic* or "sewage" or "contaminant" or "pollution" Eutrophication and Anoxia "eutrophication" or "hypoxia" Invasive Species "invasi*" or "outbreak" or "proliferation" Physical Coastal Development "land reclamation" or "sediment" or "habitat loss" or "extraction" or "depth change" Indirect Fishing Impacts "fishing" or "trawling" or "dredging" Continued higher nutrient loads may negatively impact fish populations by decreasing the cover of canopy forming vegetation (Cloern, 2001) and increasing the frequency of anoxic events (Rabalais, 2015), in turn causing increases in the mortality of early life-history stages and reducing growth rates in fish (Kornilovs, 1993;Petersen and Pihl, 1995;Maes et al, 2007;Teschner et al, 2010). In addition to the widely known direct effects of fishing on fish species, this study found that fishing often indirectly impacted fish through the destruction of biogenic structures which provide shelter (Hall-Spencer et al, 2003;Kamenos et al, 2004).…”
Section: Anthropogenic Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Relevant keywords used in search Toxicants and Pollutants "xenobiotics" or "toxic* or "sewage" or "contaminant" or "pollution" Eutrophication and Anoxia "eutrophication" or "hypoxia" Invasive Species "invasi*" or "outbreak" or "proliferation" Physical Coastal Development "land reclamation" or "sediment" or "habitat loss" or "extraction" or "depth change" Indirect Fishing Impacts "fishing" or "trawling" or "dredging" Continued higher nutrient loads may negatively impact fish populations by decreasing the cover of canopy forming vegetation (Cloern, 2001) and increasing the frequency of anoxic events (Rabalais, 2015), in turn causing increases in the mortality of early life-history stages and reducing growth rates in fish (Kornilovs, 1993;Petersen and Pihl, 1995;Maes et al, 2007;Teschner et al, 2010). In addition to the widely known direct effects of fishing on fish species, this study found that fishing often indirectly impacted fish through the destruction of biogenic structures which provide shelter (Hall-Spencer et al, 2003;Kamenos et al, 2004).…”
Section: Anthropogenic Pressurementioning
confidence: 99%
“…In terms of physical perturbations, destructive fishing methods such as bottom trawling also disrupt important fish habitats (Hiddink et al, 2006). Simultaneously, degradation of coastal fish habitats can also be brought about through eutrophication and subsequent macroalgal blooms (Rabalais, 2015;Le Luherne et al, 2016) or anoxic events (Cloern, 2001) derived from nutrient input associated with urban and agricultural activities. Other terrestrial and coastal activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This species feeds opportunistically upon a variety of prey items and thus accidental ingestion of microplastics from the water column as the fish mistakes plastic for prey is a potential concern (Sedberry 1988;Devriese et al 2015). C. striata utilize nursery habitats in estuaries and coastal waters that are notably impacted by anthropogenic activities, during their early life stages (Beck et al 2001;Rabalais 2015;Vendel et al 2017). Interspecific variation in microplastics ingestion is likely due to the species-specific feeding strategies and abundance of plastics in their surrounding environment (Lusher et al 2013, de Ruijter et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…However, life cycle approaches integrating impacts of these multiple stressors all along the life cycle remain rare. Also, less attention has been paid to the quantitative assessment of how the spatial structure of populations and patterns of connectivity along the life cycle interact with spatially structured stressors (Cianelli et al, 2013) such as coastal nursery habitat degradation (Rabalais, 2015) or spatially non-homogenous fishing effort.…”
Section: Introductionmentioning
confidence: 99%